Features of analytical control of glyphosate salts in preparative formulations - Chervyakova, L.; Panchenko, T.; Tsurkan, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. Development of a method of analytical control of glyphosate in preparative forms of herbicides. Methods. Determination of glyphosate was carried out by the chromatographic method of thin-layer chromatography (TLC) using Sorbfil plates with a thin layer of silica gel KSK adsorbent. The active substance was identified by the value of Rf, quantitative determination was based on the formalized dependence of the size of the area of the chromatographic zones on the amount of glyphosate. Results. Physicochemical properties of herbicides — electrolytes, to which glyphosate belongs, create special problems when developing methods for its determination in various matrices. In herbicides and desiccants, glyphosate (as a salt) usually takes the form of a deprotonated acid residue and a corresponding cation. Therefore, the determination of the active substance is carried out by the acid residue, which is important for the quantitative assessment of its content in the matrix both in the acid equivalent and in the form of the corresponding salt. The density of the preparative form serves, in particular, as a criterion for controlling the form of the glyphosate salt. The method is based on dissolution of the preparation form in 44% ethanol and quantitative determination by TLC method. The determination of the active substance is not hindered by other components of the preparations, derivatives of glycine and amines.The optimal conditions of analysis were chosen using the conceptual designs of the laboratory «Algorithm of chemical-analytical monitoring of pesticides» and «System of multi-quantitative determination of pesticides in matrices», according to which the main stages of the process are extraction/dissolution, purification of extracts, elution (chromatographic process), identification and quantitative analysis . Selective conditions for TLC determination — mobile phase with pH 9: distilled water + ethanol + aqueous ammonia (22 + 20 + 0.25 by volume), developing reagent: a specific complex of ninhydrin with cadmium acetate in an acidic medium. Quantitative determination is carried out taking into account the coefficients of conversion of the corresponding salt form to the acid equivalent. Conclusions. The use of the chromatographic method of thin-layer chromatography makes it possible to control the content of the active substance glyphosate in various salt formulations in preparative forms of herbicides and desiccants with high accuracy and reproducibility.